A Novel Method for Identifying and Treating Erectile Dysfunction: Pharmaceutical sciences- Pharmaceutics - Ajay Gupta, Ram; Shiven, Aditya (International Journal of Life Science and Pharma Research, 2023)
Sexual or erectile dysfunction (ED) is the ineptitude to get or keep a hard penile erection. ED can have a detrimentaleffect on physical and psychological health. This review helps in understanding the detailed etiology of ED and variousapproaches for the management of ED. The occurrence and incidence of erectile dysfunction are on the rise among men.Various other factors greatly impact the progression of ED, including individual general health and physiological conditions suchas psychiatric or psychological problems, diabetes mellitus, genitourinary disease, cardiovascular disease, and chronic diseases.Erectile dysfunction occurs when the release of nitric oxide (NO) triggers the activation of the guanylate cyclase enzyme in thespongiosum and corpora cavernosa, leading to relaxation of the vascular smooth muscle and an increase in cyclic guanosinemonophosphate (cGMP) levels. This physiological process is essential for achieving and maintaining a firm penile erection. Somecommon and advanced methods, such as the physical method, sexual history, laboratory testing, apomorphine test, NPTR test,and color duplex Doppler ultrasound test, are used to diagnose erectile dysfunction. This review also focuses on emergingtreatments that address the medical need for effective ED management. This comprehensive review bridges gaps in the currentliterature, offering superior insights into ED management and improving the quality of life for individuals with ED.